Childhood Trauma Exposure and Alcohol Dependence Severity in Adulthood: Mediation by Emotional Abuse Severity and Neuroticism - Schwandt, Melanie L.; Heilig, Markus; Hommer, Daniel W.; George, David T.; Ramchandani, Vijay A. (Alcoholism, clinical and experimental research, 2013)
Background Childhood trauma has been linked with a number of negative outcomes later in life, including alcohol dependence (AD). Previous studies have suggested a mediating role for neuroticism in the relationship between childhood trauma and psychopathology. In this study, we investigate the prevalence of multiple types of childhood trauma in treatment‐seeking alcohol‐dependent patients, and the associations between childhood trauma and AD severity using multiple mediation analysis. Methods The prevalence of 5 types of childhood trauma—emotional abuse, sexual abuse, physical abuse, emotional neglect, and physical neglect—was assessed in treatment‐seeking alcohol‐dependent patients (n = 280) and healthy controls (n = 137) using the Childhood Trauma Questionnaire. Multiple mediation analyses were used to model associations between childhood trauma measures and alcohol‐related outcomes, primarily the severity of AD in the alcohol‐dependent sample. Results Childhood trauma was significantly more prevalent and more severe in the alcohol‐dependent subjects. In addition, childhood trauma was found to influence AD severity, an effect that was mediated by neuroticism. When individual trauma types were examined, emotional abuse was found to be the primary predictor of AD severity, both directly and through the mediating effects of the impulsivity subfacet of neuroticism. Physical abuse also had a moderate direct effect on AD severity. Mediation analysis did not reveal any association between childhood trauma and Alcohol Use Disorders Identification Test score in the nondependent control sample. Conclusions Childhood trauma is highly prevalent in treatment‐seeking alcoholics and may play a significant role in the development and severity of AD through an internalizing pathway involving negative affect. Our findings suggest that alcoholics with a history of childhood emotional abuse may be particularly vulnerable to severe dependence.